Sacred songs and arias by women composers: A survey of the literature and performer's analysis of selected works by Isabella Leonarda, Luise Reichardt, Ethel Smyth, Violet Archer, Margaret Bonds and Edith Borroff - Heape, Mary Willis (Séminaire théologique baptiste du Sud-Ouest, 1995)
This document is written in support of a recital of sacred songs and arias by women composers. It is divided into two sections: a survey of sacred music, specifically sacred arts songs and sacred arias from larger works, and a performer's analysis of selected works drawn from the research of the first part. The survey begins with the commercial printing of music around 1500 and extends to 1994. Countries from around the world are represented, some more broadly than others. Biographical information, when available, is given for each composer featured in the survey as well as some discussion of her general compositional style and output. Greater attention is given to the composer's sacred music, especially compositions that involve the solo voice. Composers who wrote very little sacred music for the solo voice are mentioned only briefly. The performer's analysis includes biographical information on each composer as well as a discussion of her general style, significant compositions, honors and awards and sphere of influence. In the analysis of the pieces, attention is focused on elements in the music that affect its performance. The selected works include Volo Jesum, a solo motet by Isabella Leonarda, "An Maria," "Stille der Andacht" and "Die Blume der Blumen," three art songs by Luise Reichardt, "Benedictus" from Mass in D by Ethel Smyth, Violet Archer's Three Biblical Songs, Five Spirituals by Margaret Bonds and Missa Patrinae Rerum Domini, a setting of the mass for solo voice by Edith Borroff. The appendices include work lists of the selected composers, IPA transcriptions of the pieces, a chronological listing of composers, and a copy of the program, program notes and lecture from the recital. An extensive bibliography is included.
Keywords: Archer; Bonds; Borroff; Communication and the arts; Edith; England; Ethel; Germany; Isabella; Leonarda; Luise; Margaret; Reichardt; Smyth; Social sciences; Violet

Expressive Modes in the Judeo-Spanish Wedding Song - Anahory-Librowicz, Oro (New Horizons in Sephardic Studies, 1993)

The Music of the Songs: Musical Transcriptions and Commentary of the Songs Discussed by Oro Anahory-Librowicz "Expressive Modes in the Judeo-Spanish Wedding Song" - Cohen, Judith R. (New Horizons in Sephardic Studies, 1993)

Quel plain-chant pour la Nouvelle-France ? L'exemple des Ursulines - Pinson, Jean-Pierre (Canadian University Music Review, 1991)
S'il est une musique qui fut pratiquée en Nouvelle-France depuis les origines jusqu'au XXe siècle, ce fut bien celle du plain-chant1. Or, ce répertoire se présente comme un reflet souvent exact du plain-chant gallican, de son histoire et de sa pratique. Certes, il lui a fallu s'adapter aux lieux, aux populations et aux coutumes, mais sa répartition géographique, moins complexe qu'en France, et le nombre plus restreint d'institutions et de paroisses permettent une méthode d'approche à peu près contrôlable. Au cours de notre projet de recherche2, nous avons recueilli à travers le Québec des centaines de sources qui tracent un portrait riche de cette pratique. Mieux : au-delà du plain-chant lui-même c 'est en fait le chant baroque français qui s'est conservé longtemps ici, « sous cloche », dans un milieu très conservateur : ce chant de la Nouvelle-France est un beau cas de Performing practice. Parmi toutes les institutions visitées, les Ursulines de Québec et de Trois-Rivières3 constituent une excellente illustration de ce phénomène. Les sources conservées chez elles, classées dans l'annexe bibliographique, présentent une synthèse assez fidèle des sources demeurées en Nouvelle-France, contribuant ainsi à l'élaboration de ce portrait.

Sur les traces de Dina. Dina Bélanger, 1897-1929 - Boucher, Ghislaine (Les Religieuses de Jésus-Marie, 1990)

La formation professionnelle des filles dans les écoles supérieures de musique tenues par les religieuses, 1926-1960 - Mendez, Manon (Université de Sherbrooke, 1990)

"Ya salio de la mar": Judeo-Spanish Wedding Songs among Moroccan Jews in Canada - Cohen, Judith R. (Women and Music in Cross-Cultural Perspective, 1989)

Les Ursulines et la musique - Gréroire-Reid, Claire; V. -Demers, Micheline (Cap-aux-Diamants : la revue d'histoire du Québec, 1989)

Place aux femmes-compositeurs du Québec - Lefebvre, Marie-Thérèse (Les Cahiers de l'ARMuQ, 1988)

Exposition au monastère des Ursulines de Québec - Grégoire-Reid, Claire; Vézina-Demers, Micheline (Les Cahiers de l'ARMuQ, 1987)

La création musicale chez les religieuses de trois communautés montréalaises - Rhéaume, Claire (Université de Montréal, 1987)

Dina Bélanger, Marie Sainte-Cécile-de-Rome, 1897-1929. Itinéraire spirituel - Boucher, Ghislaine (Éditions Paulines, 1983)

Une missionnaire de la musique : Sœur Marie-Stéphane, S.N.J.M. fondatrice de l'école Vincent-D'Indy - Millette, Juliette (Cahier de la Société historique de Montréal, 1982)

L'enseignement de la musique vocale et instrumentale aux Ursulines de Québec de 1830 à 1880 - Pagé, Thérèse (Université Laval, 1975)

L'histoire de la musique de l'Institut des Sœurs de la Charité de Québec - Roy, Marielle (Université Laval, 1968)